2015
DOI: 10.1111/liv.13005
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics are helpful in hepatic encephalopathy: a meta‐analysis of randomized trials

Abstract: Overall the use of probiotics was more effective in decreasing hospitalization rates, improving MHE and preventing progression to OHE in patients with underlying MHE than placebo, but similar to that seen with lactulose. The use of probiotics did not affect mortality rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 45 publications
3
40
0
Order By: Relevance
“…covert) HE 60. However, these effects were not observed when probiotic use was compared to lactulose.…”
Section: Other Treatment Regimensmentioning
confidence: 93%
“…covert) HE 60. However, these effects were not observed when probiotic use was compared to lactulose.…”
Section: Other Treatment Regimensmentioning
confidence: 93%
“…Hepatic Encephalopathy: Probiotics seem to be effective for the treatment of hepatic encephalopathy. A meta-analysis of six RCTs involving 496 adults with cirrhosis showed that probiotic therapy significantly reduced the development of overt hepatic encephalopathy (Saab et al, 2015).…”
Section: Evidence For the Therapeutic Use Of Probioticsmentioning
confidence: 99%
“…More recently, nascent data have been emerging on the use of probiotics to treat HE and have shown improved quality of life in these patients, but mortality benefits are still unclear with use of probiotics, and available quality of evidence is still low. 76,77 PPIs have been shown to be associated with development of HE. 78,79 Patients prescription list should be checked for PPI, and PPIs should be discontinued unless there is a clear indication for their use.…”
Section: Hepatic Encephalopathymentioning
confidence: 99%